Risk assessment of data asset management based on fuzzy hierarchy method and association rules - Chen Shuguo; Wu Yaomao; Fu Yue; Zhang Yihong (SHS Web of Conferences, 2023)
In the current data asset management risk assessment, the processing of assessment indicators is relatively simple, which leads to large errors in the assessment results. To this end, a data asset management risk assessment based on fuzzy hierarchy method and association rules is proposed. Identify risk factors for data asset management. Construct a risk assessment model. Quantify the model indicators based on the fuzzy hierarchy method, generate a judgment matrix and derive a comprehensive assessment vector. Assess risk levels based on association rules. Experiments show that the risk level assessment of the method has a correct rate of 100% and the assessment error of the risk score is 1.86 points, which has high application value.